Supplemental Material: Geochronology of the Wrangell Arc: Spatial-temporal evolution of slab edge magmatism along a flat slab subduction-transform transition, Alaska-Yukon - J.M. Trop (11273695); (281964) (2021)
Item S1: Physiographic aspects of the Wrangell Arc that make bedrock sampling challenging, including scale of eruptive centers and glaciated, rugged, roadless terrain. Item S2: Photomicrographs of representative sand samples from modern rivers showing abundant volcanic lithic grains. Item S3: Modern river sediment sample location information. Item S4: Methods for calculating watershed boundaries, surface area of ice, surficial deposits, and bedrock, and geochronologic samples. Item S5: Summary of surface area of ice, surficial deposits, and bedrock within sampled watersheds. Item S6: 40 Ar/ 39 Ar and U-Pb analytical details. Item S7: New igneous bedrock 40 Ar/ 39 Ar fusion data. Item S8: Previously reported igneous bedrock data. Item S9: Detrital cobble-sized 40 Ar/ 39 Ar (DARL) fusion data. Item S10: Detrital sand-sized 40 Ar/ 39 Ar (DARL) step-heat data. Item S11: Detrital sand-sized volcanic-lithic 40 Ar/ 39 Ar (DARL) fusion data. Item S12: Detrital zircon (DZ) U-Pb age data. Item S13: Examples of differences between detrital zircon (DZ) vs. volcanic lithic (DARL) dates.